TYPES OF STUDENT TRANSLATION ERRORS IN ENGLISH-INDONESIAN TRANSLATION - Dewi, Haru Deliana; Wijaya, Andika (Paradigma: Jurnal Kajian Budaya, 2025)
This research focuses on translation and language errors discovered in English-Indonesian translation results. This study aims to investigate the types of errors mostly made by Indonesian novice translators. The data were obtained from translation practice assigned to undergraduate students, who were taking the compulsory basic translation course. The respondents, who were native Indonesian speakers, were asked to translate two paragraphs from a given text in class for one hour and send their translations to the raters via email. The raters then marked the errors in the students’ translations using the 2021 ATA’s Standardized Framework for Error Marking. The results of the study show that the most frequent errors made by the participants were spelling and terminology errors, which might be simply caused by sloppiness or by the participants’ lack of knowledge of the proper official Indonesian spelling system and which could be due to their ignorance of the proper terms.